Development Gap Between Rural and Urban Stabilizers - Noor Ali Rishak; Muheeb K. Fleih Al-Rawy (College of Education for Women, 2019)
This research concluded that after what has been presented an analysis of the topics that the process of measuring the level of development and then the development gap is the need to assess the results to set policy and to formulate plans and goals, and to see the development priorities of the place or a particular sector. The purely economic development led to negative effects on the spatial scale and the most important of these effects arise multidimensional social and urban development gaps as well as the economic dimension. So it must exceed the concept of economic framework, to include all dimensions of development spatially and sectorally to provide correct and clear base for planners and development policies and strategies for developers, and specialists to jump-start them in setting priorities and guiding the development process in the framework of balance and social justice The communities that followed the industrialization and urbanization methods, any unbalanced growth pushed the urban areas to the depletion of resources in rural areas and degradation socially, economically, environmentally and spatially although it did not achieve the economic growth that parallels the population increases excessive. It said most of the settlements served the development of problems related to the steady increase in population growth and the inability of development plans to cope with the dynamics of that growth quantified and spatially. Urbanization, which is economically positive have a negative impact on environmental and social sustainability, and are at the expense of larger areas of the spatial extent. You can control it and reduce it if urbanization is happening within sustainable frameworks, leading to the development and growth and greater connectivity and interdependence between rural and urban settlements served -oho of issues of direct relevance to reducing the development gap between the settlements served. The migration (rural out) of the most prominent aspects of the development gap, which has a lot of negative economic, social and environmental impacts. It can not be regarded as a fundamental problem of resource scarcity in the palaces of the development process, but also in people's inability to optimize the use of what is available including, abandoning the permanent tender resources and head to overpopulation areas. A major factors causing the stagnation of resources and rigidity of development, especially the weakness of government investment and the deterioration of the reality of the infrastructure and the low level of professional and vocational specialization and economic ignorance resulting from the lack of awareness and economic culture, and weak technical and technological knowledge and development management.